France and the American Civil War : a diplomatic history - Sainlaude, Stève (Civil War America (Series), 2019)
France's involvement in the American Civil War was critical to its unfolding, but the details of the European power's role remain little understood. Here, Stève Sainlaude offers the first comprehensive history of French diplomatic engagement with the Union and the Confederate States of America during the conflict. Drawing on archival sources that have been neglected by scholars up to this point, Sainlaude overturns many commonly held assumptions about French relations with the Union and the Confederacy. As Sainlaude demonstrates, no major European power had a deeper stake in the outcome of the conflict than France.